Simulation of screw–press oil extraction as a set of two processes: incompressible viscous mixture flow and fluid filtration in porous medium - Petrov, Ilia Andreevich; Slavnov, Evgeniy Vladimirovich (Computational Continuum Mechanics, 2013)
A model of oil extraction with a screw extruder has been developed in terms of integral characteristics. The model considers the process of oil extraction as a set of two processes: the flow of viscous mixture and the filtration of the liquid component in the processed material. The design of numerical experiment has been worked out in accordance with an orthogonal central composite design. Simulation of rapeseed oil extraction has been carried out for different parameters of the screw extruder using the experimentally obtained dependence of the rape permeability coefficient on oil concentration and pressure level of the extruder. The coefficients of regression equations have been found for the functions of oil output, specific energy and residual mass oil concentration. The effects of the geometrical parameters of the extruder and the rotational speed of the screw on the values examined have been estimated.
Keywords: screw extrusion machine; extraction; extrusion; permeability coefficient; rape; rape oil; mathematical model